The effectiveness of Social Media Instagram as a Promotion of Agricultural product of fruits. (case :Instagram TaniHub Indonesia, Pasar Minggu, Jakarta Selatan) - Nensy Yohana Natalia Pasaribu (Jurnal Sains Komunikasi dan Pengembangan Masyarakat [JSKPM], 2020)
Agriculture produces processed product which is perishable, so that the agricultural product should be distributed immediately. Processed product can be promoted to attract consumers to buy the product. One of the media that can be used to promote processed agricultural product is social media. Social media is needed to ease the marketing activity on the product. Social media is viral and can be delivered directly and personally to the consumer. Indicators are used to know the effectiveness of the social media as promotion media with AIDA concept. The results showed that promotion through Instagram has not been effective in the stages of attention (attention), interest (interest), desire (desire), and action (action). This study also explains that there is a relationship between the characteristics of gender followers and the level of social media exposure to the frequency of messages. In addition, there is also a relationship between the frequency of message feedback, message attractiveness, and intelligence in delivering messages with the interest stage.